Gender Relations in the Church: A Call to Wholeness and Equal Discipleship - Anand, Subhash (Asian Horizons, 2012)
Astrid Lobo Gajiwala, Varghese Theckanath, S.G, & Raynah Braganza Passanha, ed., Gender Relations in the Church: A Call to Wholeness and Equal Discipleship, Delhi: Media House (Jointly published by Streevani, Pune and Montfort Social Institute, Hyderabad), 2012. ISBN:978-81-7495-4690. Pages 248.